A comparison of service organisation and guideline compliance between two adjacent European health services. (September 2017) - McElwaine, Paul; McCormack, Joan; McCormick, Michael; Rudd, Anthony; Brennan, Carmel; Coetzee, Heather; Cotter, Paul E; Doyle, Rachel; Hickey, Anne; Horgan, Frances; Loughnane, Cliona; Macey, Chris; et al.
Introduction: Outcomes in stroke patients are improved by a co-ordinated organisation of stroke services and provision of evidence-based care. We studied the organisation of care and application of guidelines in two neighbouring health care systems with similar characteristics. Methods: Organisational elements of the 2015 National Stroke Audit (NSA) from the Republic of Ireland (ROI) were compared with the Sentinel Stroke National Audit Programme (SSNAP) in Northern Ireland (NI) and the United Kingdom (UK). Compliance was compared with UK and European guidelines. Results: Twenty-one of 28 ROI hospitals (78%) reported having a stroke unit (SU) compared with all 10 in NI. Average SU size was smaller in ROI (6 beds vs. 15 beds) and bed availability per head of population was lower (1:30, 633 vs. 1:12, 037 p < 0.0001 Chi Sq). Fifty-four percent of ROI patients were admitted to SU care compared with 96% of UK patients ( p < 0.0001). Twenty-four–hour physiological monitoring was available in 54% of ROI SUs compared to 91% of UK units ( p < 0.0001). There was no significant difference between ROI and NI in access to senior specialist physicians or nurses or in SU nurse staffing (3.9/10 beds weekday mornings) but there was a higher proportion of trained nurses in ROI units (2.9/10 beds vs. 2.3/10 beds ( p = 0.02 Chi Sq). Conclusion: Whilst the majority of hospitals in both jurisdictions met key criteria for organised stroke care the small size and underdevelopment of the ROI units meant a substantial proportion of patients were unable to access this specialised care.